2017
DOI: 10.1002/ejic.201700377
|View full text |Cite
|
Sign up to set email alerts
|

Bis(selone) Complexes of Palladium(II), Platinum(II), and Gold(III): Synthesis and Structural Studies

Abstract: New bis(selone)‐based metal complexes, [MnLxCly] {M = Pd, L = 3,3′‐[(2‐bromo‐1,3‐phenylene)bis(methylene)]bis(1‐mesityl‐1,3‐dihydro‐2H‐imidazole‐2‐selone) (15), n = 2, x = 2, y = 4, C64H66N8Cl4Br2Se4Pd2) (17); M = Pt, L = 15, n = 2, x = 2, y = 4, C64H66N8Cl4Br2Se4Pt2 (18); M = Au, L = 15, n = 1, x = 1, y = 1, C32H33N4Se2BrAuCl (19)} were synthesized by the reaction of bis(selone) (15) with Pd(COD)Cl2 (yield 31 %), Pt(COD)Cl2 (yield 34 %), and [AuCl(SMe2)] (yield 57 %), respectively. Single‐crystal X‐ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Taking this interaction into consideration, the overall packing of structure 3 can be described as a coordination polymer with trimetallic repeat units as depicted in Figure 5. In all cases, the 1 H and 13 C NMR spectra showed evidence of a single aromatic environment, whereas the solid-state structures exhibit two inequivalent environments. Thus, the solid-state structures do not appear to persist in methanolic solution and the complexes either adopt a new structural motif, undergo dynamic exchange on the NMR timescale, or possibly both.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Taking this interaction into consideration, the overall packing of structure 3 can be described as a coordination polymer with trimetallic repeat units as depicted in Figure 5. In all cases, the 1 H and 13 C NMR spectra showed evidence of a single aromatic environment, whereas the solid-state structures exhibit two inequivalent environments. Thus, the solid-state structures do not appear to persist in methanolic solution and the complexes either adopt a new structural motif, undergo dynamic exchange on the NMR timescale, or possibly both.…”
Section: Resultsmentioning
confidence: 87%
“…Chemical shifts are reported in parts per million (ppm); J values are given in hertz (Hz). 1 H and 13 C resonances are referenced to residual proton-containing species within the deuterated solvent or the deuterated solvent itself using reported values, 34 relative to SiMe4. 19 F and 77 Se NMR spectra were referenced externally using C6F6 in CDCl3 ( −164.9) and Ph2Se2 in CDCl3 ( 463) relative to CFCl3 and SeMe2, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reveal the working mechanism of the selective extraction of Au 3+ , the XPS spectra of N 1s and Se 3d were measured for P2 before and after coordinating with Au 3+ and drying in an oven at 40°C. While the XPS spectra of N 1s showed no change, the binding energy of Se 3d shifted from 54.25 to 55.77 eV (Supporting Information Figure S20), indicating strong coordination between the Se atom and Au 3+ , attributable to interchain cross-linking ( Figure 4c) [50][51][52] and a possibility of redox reaction during drying in the oven.…”
Section: Kinetic Study Of the Mcpmentioning
confidence: 99%
“…Selones, the Se-analogues of ketones, have generated considerable interest due to their promising utility in many domains, including homogeneous catalysis (see for example: Prabhu et al Recently, our group has reported the syntheses and crystal structures of [2 + 2] binuclear palladium(II) and platinum(II) self-assembled 24-membered metallomacrocycles resulting from the reaction Pd(COD)Cl 2 and Pt(COD)Cl 2 with 3,3 0 -[(2-bromo-1,3-phenylene)bis(methylene)]bis(1-mesityl-1,3-dihydro-2H-imidazole-2-selone), and of a mononuclear gold(III) complex formed with AuCl(SMe 2 ) (Rani et al, 2017). Herein, we report on the synthesis and crystal structure of the related title compound, 3,3 0 -[(2-bromo-1,3-phenylene)bis(methylene)]bis(1-butyl-2,3-dihydro-1H-imidazole-2-selone).…”
Section: Structure Descriptionmentioning
confidence: 99%